Global Financial Stability Report, October 2020 : Bridge to Recovery. (Global Financial Stability Report; Global Financial Stability Report, 2020)
Near-term global financial stability risks have been contained as an unprecedented policy response to the coronavirus (COVID-19) pandemic has helped avert a financial meltdown and maintain the flow of credit to the economy. For the first time, many emerging market central banks have launched asset purchase programs to support the smooth functioning of financial markets and the overall economy. But the outlook remains highly uncertain, and vulnerabilities are rising, representing potential headwinds to recovery. The report presents an assessment of the real-financial disconnect, as well as forward-looking analysis of nonfinancial firms, banks, and emerging market capital flows. After the outbreak, firms' cash flows were adversely affected as economic activity declined sharply. More vulnerable firms-those with weaker solvency and liquidity positions and smaller size-experienced greater financial stress than their peers in the early stages of the crisis. As the crisis unfolds, corporate liquidity pressures may morph into insolvencies, especially if the recovery is delayed. Small and medium-sized enterprises (SMEs) are more vulnerable than large firms with access to capital markets. Although the global banking system is well capitalized, some banking systems may experience capital shortfalls in an adverse scenario, even with the currently deployed policy measures. The report also assesses the pandemic's impact on firms' environmental performance to gauge the extent to which the crisis may result in a reversal of the gains posted in recent years.